Impacts of Simulated Weightlessness by Dry Immersion on Optic Nerve Sheath Diameter and Cerebral Autoregulation - Kermorgant, Marc; Leca, Florian; Nasr, Nathalie; Custaud, Marc-Antoine; Geeraerts, Thomas; Czosnyka, Marek; Arvanitis, Dina N.; Senard, Jean-Michel; Pavy-Le Traon, Anne (Frontiers in Physiology, 2017)
Dry immersion (DI) is used to simulate weightlessness. We investigated in healthy volunteers if DI induces changes in ONSD, as a surrogate marker of intracranial pressure (ICP) and how these changes could affect cerebral autoregulation (CA). Changes in ICP were indirectly measured by changes in optic nerve sheath diameter (ONSD). 12 healthy male volunteers underwent 3 days of DI. ONSD was indirectly assessed by ocular ultrasonography. Cerebral blood flow velocity (CBFV) of the middle cerebral artery was gauged using transcranial Doppler ultrasonography. CA was evaluated by two methods: 1) transfer function analysis was calculated to determine the relationship between mean CBFV and mean arterial blood pressure (ABP) and 2) correlation index Mxa between mean CBFV and mean ABP.ONSD increased significantly during the first day, the third day and the first day of recovery of DI (P < 0.001).DI induced a reduction in Mxa index (P < 0.001) and an elevation in phase shift in low frequency bandwidth (P < 0.05). After DI, Mxa and coherence were strongly correlated with ONSD (P < 0.05) but not before DI. These results indicate that 3 days of DI induces significant changes in ONSD most likely reflecting an increase in ICP. CA was improved but also negatively correlated with ONSD suggesting that a persistent elevation ICP favors poor CA recovery after simulated microgravity.